*** the best answer ***
r+3(-6r+r)
r+3(-5r)
r-15r
-14r
2006-10-10 09:35:50
·
answer #1
·
answered by Anonymous
·
2⤊
1⤋
-4r + 3 and -5a + -12 and dont overlook the negatives. upload r+ -6r + yet another r. r+ -6r= -5r+ yet another r = 4r and dont overlook the + 3. in the parenthasis multiply the two by -4 which equals -4a + -12 -a which makes it -5a + -12.
2016-12-26 15:27:02
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
Simplify like terms. (-6r+r) = -5r
Multiply the terms that can be multiplied. r+3(-5r) = r+-15r
Now add you like terms. r+-15r = -14r
ANSWER = -14r
2006-10-10 09:46:32
·
answer #3
·
answered by breanna_marie_wilson 1
·
0⤊
0⤋
that's a factorization, you just multiply:
-6r^2 + r^2 -18r + 3r
and simplify: -5r^2 - 18r + 3r
2006-10-10 09:41:04
·
answer #4
·
answered by icez 4
·
0⤊
0⤋
Order of operations. Do stuff in parenthesis first.
r + 3*(-5r)
Then multiply
r -15r
-14r
2006-10-10 09:41:40
·
answer #5
·
answered by Mee 4
·
0⤊
0⤋
r + 3 (-6r + r) = r -18r + 3r = -14r
2006-10-10 09:38:21
·
answer #6
·
answered by Danny B 3
·
1⤊
0⤋
r+3(-6r+r)
r+3(-5r)=r-15r=-14r
2006-10-13 08:49:12
·
answer #7
·
answered by yupchagee 7
·
0⤊
0⤋
r+3(-6r+r)
r-18r+3r
-14r
2006-10-10 09:42:03
·
answer #8
·
answered by nor2006 3
·
0⤊
0⤋
r + 3(-6r + r)
r + (-18r + 3r)
r + (3r - 18r)
r + ( - 15r)
= -14r
2006-10-10 10:18:54
·
answer #9
·
answered by Brenmore 5
·
0⤊
0⤋
=r+3(-5r)
=-5r2-15r
r=0
or
r=-3
if quadratic equation
OR
r lies between 0 and -3
2006-10-10 09:41:55
·
answer #10
·
answered by chumbawamba 1
·
0⤊
0⤋